Pemanfaatan Web Bagi Dosen Prodi Pendidikan Seni Pertunjukan Pada Masa Covid 19 - Aline Rizky Oktaviari Satrianingsih; Imam Ghozali; Mega Cantik Putri Aditya; Zakarias Aria Widyatama; Mastri Dihita Sagala (Universitas PGRI Palembang, 2023)
The COVID-19 pandemic had a major impact on the world of education in Indonesia. Face-to-face learning has become something that cannot have been done because everyone has shifted to online learning. This caused the learning process to stop because several things needed to be prepared both internally and externally. Lecturers are teaching staff in the academic environment who must be prepared to face the pandemic, so that students will not experience delays in the lecture process. Utilizing the WEB using E-Learning can be utilized optimally in online learning unconditionally. The Performing Arts Education Study Program collaborates with the UNTAN E-Learning Team to gived outreach and training to lecturers and teaching staff. This socialization and training is carried out in 5 steps consisting of; 1) Lecture; 2) Questions and Answers; 3) Demonstration; 4) Practice; and5) Mentoring. The implementation of this activity has an impact on increasing the understanding and application of the web by lecturers at the Performing Arts Education Study Program, FKIP, Tanjungpura University. This can be seen from the activeness of lecturers who upload material and activities in UNTAN E-Learning according to the courses to be implemented